(untitled) (The Proceedings of The International Conference on Climate Change, 2022)
Nutrient leaching causes agronomic and environmental problems in intensively cultivated soils. In this study, the effect of biochar on retension of nutrient in sandy loam soil was evaluated. Upland rice was amended with 3 different sources of biochar in randomized complete design with 4 replications. The treatment included a control (no input), fertilizer, and upland rice either applied alone or in combination with the three different sources of biochar (poultry manure, corn cobs and groundnut shell). Biochar levels were 5 t ha-1 each and were incorporated into the soil at the same time. Inorganic fertilizer was applied at a rate of 90, 60, 60 and 45, 30, 30 kg ha-1 NPK, as straight fertilizer and then top-dress with nitrogen levels in the form of urea 30 kg ha-1 N eight (8) weeks after transplanting. Upland rice was planted in each lysimeter. Leachate from each lysimeter was collected at 3 weeks intervals for 24 months. For the 24 months running biochar significantly decreased the volume of water leached. Control and 90N60P60K treatments showed higher concentrations of NO3-N and K in the leachate. At a depth of 70 cm leaching significantly reduced with all the three different sources of biochar combined with 45N30P30K and 90N60P60K. The application of three different biochar sources to tropical sandy loam soil may give environmental benefits such as carbon sequestration and reduced nitrate and potassium leaching. Our results indicated that biochar and 45N30P30K combination could be appropriate as a sustainable agronomical approach.